C66 LONG TERM FOLLOW–UP OF PATIENTS WITH BIOPSY– PROVEN DIAGNOSIS OF MYOCARDITIS AND VENTRICULAR ARRHYTHMIAS. (18th May 2022) - Lavalle, C; Magnocavallo, M; Mariani, M; Vetta, G; Della Rocca, D; Alfarano, M; Piro, A; Natale, A; Fedele, F; Vizza, D; Frustaci, A; Chimenti, C
Abstract: Background: The diagnosis and management of patients with myocarditis with ventricular arrhythmic (VA) onset is one of the major challenging issues faced by physicians. Objective: We aimed at evaluating the natural history of patients with an endomyocardial biopsy–proven diagnosis of myocarditis with a VA manifestation at the time of diagnosis. Methods: From January 2013 to October 2021, 243 consecutive patients with unexplained VAs underwent a complete diagnostic work–out, including endomyocardial biopsy. All patients with a biopsy–proven diagnosis of myocarditis were included in the study. Results: 104 patients were enrolled (mean age: 54 ± 16 years; 75% male). The presenting arrhythmic manifestation was syncope/aborted sudden death in 21 (20.2%) patients, sustained ventricular tachycardia (VT) in 16 (15.4%), nonsustained VT in 29 (27.9%) and frequent premature ventricular complexes in 38 (36.5%). Patients with severe systolic dysfunction (Ejection Fraction<35%) were 63.5%. Late gadolinium enhancement (LGE) and myocardial oedema were detected at cardiac magnetic resonance (CMR) in 91.8% and 30% patients, respectively. Thirty–eight (36.5%) patients received an implantable cardioverter defibrillator (ICD) for primary (n = 14; 36.8%) or secondary (n = 24; 63.2%) prevention of sudden cardiac death (SCD). The mean follow–up was 69 ± 32 months: cardiovascular (CV) death was 15.4% while the recurrence of sustained Vas was 27.9%. Among ICD patients, 13 (34.2%) had an appropriated therapy of the device and arrhythmic storm occurred in 3 (23.1%) of them. The combined endpoint of sustained VA/ICD therapy/CV death occurred in 35.6%. The most important independent predictor of VAs was the presence of LGE [Odds Ratio: 9.100; Confidence of Interval: 1.125 – 73.609; p–value: 0.04]. Conclusion: Among patients with a diagnosis of myocarditis and VAs, 35.6% had recurrences of VA/ICD therapy/CV death during follow–up. The presence of LGE at CMR stratifies the risk of VA recurrence.